Study of Some Biochemical Parameters Related to Heart Function in Ascending and Descending Effort - Dhiaa Kasim Al-Khayat; Luay Abed Al-Helaly; Hadeel Tariq Al-Taee (Tikrit Journal of Pure Science, 2023)
This research is carried out to study the effect of ascending and descending effort on some biochemical parameters related to heart function which include: Arterial natriuretic hormone, angiotensin II, sodium, potassium, lactate dehydrogenase, creatine kinase, aspartate aminotransferase, adiponectin, lipase, triglycerides, free fatty acid, lipooxygenase and myeloperoxidase . The major samples included (15) of the track and field players participating in Mosul university team of middle-distance runners .